Unraveling consequences of soil micro- and nano-plastic pollution on soil-plant system: Implications for nitrogen (N) cycling and soil microbial activity - Iqbal, S.; Xu, J.C.; Schaefer, D.A.; Khan, S.; Nadir, S.; Arif, M.S.; Yasmeen, T. (Elsevier, 2020)
Micro- and nano-plastics have widely been recognized as major global environmental problem due to its widespread use and inadequate waste management. The emergence of these plastic pollutants in agroecosystem is a legitimate ecotoxicological concerns for food web exchanges. In agriculture, micro/nano plastics are originated from a variety of different agricultural management practices, such as the use of compost, sewage sludge and mulching. A range of soil properties and plant traits are affected by their presence. With the increase of plastic debris, these pollutant materials have now begun to demonstrate serious implications for key soil ecosystem functions, such as soil microbial activity and nutrient cycling. Nitrogen (N) cycle is key predictor of ecological stability and management in terrestrial ecosystem. In this review, we evaluate ecological risks associated with micro-nano plastic for soil-plant system. We also discuss the consequence of plastic pollutants, either positive or negative, on soil microbial activities. In addition, we systematically summarize both direct and hypothesized implications for N cycling in agroecosystem. We conclude that soil N transformation had showed varied effects resulting from different types and sizes of plastic polymers present in soil. While mixed effects of microplastic pollution on plant growth and yield have been observed, biodegradable plastics have appeared to pose greater risk for plant growth compared to chemical plastic polymers.